Insulin-like growth factor 2 enhances regulatory T-cell functions and suppresses food allergy in an experimental model - Yang, Gui; Geng, Xiao-Rui; Song, Jiang-Ping; Wu, Yingying; Yan, Hao; Zhan, Zhengke; Yang, Litao; He, Weiyi; Liu, Zhi-Qiang; Qiu, Shuqi; Liu, Zhigang; Yang, Ping-Chang (Journal of allergy and clinical immunology, 2014)
The functions of regulatory T (Treg) cells are important in immunity, and the regulatory mechanisms of Treg cell activities are not fully understood yet. We sought to investigate the role of insulin-like growth factor (IGF) 2 in the upregulation of Treg cell function. The expression of insulin-like growth factor 2 receptor (IGF2R) on T cells was assessed by using flow cytometry. Treg cell functions were evaluated by assessing the suppressor effect on proliferation of other effector T (Teff) cells. The effect of IGF2 on regulating Treg cell functions were evaluated with a cell-culture model and a food allergy mouse model. Expression of IGF2R was observed in more than 90% of murine and human Treg cells but in less than 10% of effector CD4+ T cells. Activation of IGF2R and T-cell receptor induced marked Treg cell proliferation and release of TGF-β from Treg cells, which enhanced Treg cell immune suppressor effects on other Teff cell activities and allergic inflammation in the intestine. Activation of IGF2R enhances Treg cell functions in suppressing other Teff cell activities and inhibiting allergic inflammation in the intestine.